2014
DOI: 10.1039/c3ob42417k
|View full text |Cite
|
Sign up to set email alerts
|

Selective aliphatic carbon–hydrogen bond activation of protected alcohol substrates by cytochrome P450 enzymes

Abstract: Protected cyclohexanol and cyclohex-2-enol substrates, containing benzyl ether and benzoate ester moieties, were designed to fit into the active site of the Tyr96Ala mutant of cytochrome P450cam. The protected cyclohexanol substrates were efficiently and selectively hydroxylated by the mutant enzyme at the trans C-H bond of C-4 on the cyclohexyl ring. The selectivity of oxidation of the benzoate ester protected cyclohexanol could be altered by making alternative amino acid substitutions in the P450cam active s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 63 publications
0
6
0
1
Order By: Relevance
“…The position of the substrate and SOM preferences may be changed by mutations [ 67 , 68 , 69 ] and by interactions with allosteric effectors [ 6 , 26 , 44 , 70 ]. Vice versa, concentration-dependent changes in the SOM ratio due to the presence of various compounds can be used as a direct indication of ability of these compounds to serve as allosteric effectors.…”
Section: Discussionmentioning
confidence: 99%
“…The position of the substrate and SOM preferences may be changed by mutations [ 67 , 68 , 69 ] and by interactions with allosteric effectors [ 6 , 26 , 44 , 70 ]. Vice versa, concentration-dependent changes in the SOM ratio due to the presence of various compounds can be used as a direct indication of ability of these compounds to serve as allosteric effectors.…”
Section: Discussionmentioning
confidence: 99%
“…[26] Similarly, Bell and co-workers achieved the selective 4-hydroxylation of ester-o re ther-protected cyclohexanols. [27] Very impressive changes in the regioselectivity of aP 450 monooxygenasecatalysed hydroxylation of macrolides have been achieved with this approach (Scheme 8). [28] Aside from the selectivity issues,P 450 monooxygenase reactions also suffer from the generally low turnover numbers of the oxyfunctionalisation catalysts.…”
Section: 1mentioning
confidence: 99%
“…Early contributions by Griengl and co‐workers demonstrated that the hydroxylation of cyclopentanone does not occur using the P450 monooxygenase from Beauveria bassiana whereas the corresponding spirooxazolidine was converted rather efficiently . Similarly, Bell and co‐workers achieved the selective 4‐hydroxylation of ester‐ or ether‐protected cyclohexanols . Very impressive changes in the regioselectivity of a P450 monooxygenase‐catalysed hydroxylation of macrolides have been achieved with this approach (Scheme )…”
Section: Oxidation Of C−h Bondsmentioning
confidence: 99%
“…In ihren bahnbrechenden Arbeiten konnten Griengl und Mitarbeiter zeigen, dass die entsprechenden Spirooxazolidine allerdings sehr gut umgesetzt werden . Neuere Arbeiten aus dem Arbeitskreis Bell erweitern dieses Konzept auf die selektive 4‐Hydroxylierung Ether‐ oder Ester‐geschützter Cyclohexanole …”
Section: Oxidation Von C‐h‐bindungenunclassified